Design and the cation-templated self-assembly on the [MoOS3Cu3]+ based supramolecular polymeric clusters - Zhang, Zhen-Hua; Wang, Hong-Mei; Niu, Yun-Yin; Wu, Ben-Lai; Ng, Seik Weng; Hou, Hong-Wei (Elsevier, 2011)
Organic cation-templated self-assembly of 4,4′-bipy (4,4′-bipy = 4,4′-bipyridine) with [NH4]2MS2O 2 (M = Mo, W) and CuX (X = I) in the presence of bppt [bppt = 1, 5-bis (pyridinium) pentane] resulted in two novel neutral heterothiometallic cluster polymers: {[Mo2O2S6Cu 6BrI(4,4′-bipy)4] (4,4′-bipy)}n (1) and {[WOS3Cu3Br(4,4-bipy)2.5]•3 (DMF)}n (2). Compound 1 exhibits a neutral 3D 3-fold interpenetrating motif and compound 2 possesses a neutral 3D 4-fold interpenetrating architecture. Both of them have been characterized by IR, elemental analysis, TGA, UV-vis, PXRD, and single-crystal X-ray diffraction. The results may provide fascinating insights into the usage of template effect on the construction of the cluster-based coordination polymers. © 2011 Elsevier B.V. All rights reserved.